2014
DOI: 10.1007/s11033-014-3056-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of 5-enolpyruvylshikimate-3-phosphate synthase gene from Convolvulus arvensis L.

Abstract: 5-Enolpyruvylshikimate-3-phosphate synthase (EPSPS), the target enzyme for glyphosate inhibition, catalyzes an essential step in the shikimate pathway for aromatic amino acid biosynthesis. The full-length cDNA of 1,751 nucleotides (CaEPSPS, Genbank accession number: EU698030) from Convolvulus arvensis was cloned and characterized. The CaEPSPS encodes a polypeptide of 520 amino acids with a calculated molecular weight of 55.5 kDa and an isoelectric point of 7.05. The results of homology analysis revealed that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The transcription level showed that the aroA gene is expressed extensively in roots, stems, and leaves, being most highly expressed in the leaf. This expression model is consistent with the aroA expression observed in Convolvulus arvensis L. and Camptotheca acuminate (Gong et al, 2006;Huang et al, 2014). Glyphosate treatment could induce a significant increase of aroA gene expression level.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The transcription level showed that the aroA gene is expressed extensively in roots, stems, and leaves, being most highly expressed in the leaf. This expression model is consistent with the aroA expression observed in Convolvulus arvensis L. and Camptotheca acuminate (Gong et al, 2006;Huang et al, 2014). Glyphosate treatment could induce a significant increase of aroA gene expression level.…”
Section: Discussionsupporting
confidence: 89%
“…In this experiment, the peak induction was 36 h after spraying glyphosate, which was 3-fold higher than the control group's expression level. In field bindweed, the expression level of EPSPS was also responsive to glyphosate (Huang et al, 2014). These results show that the aroA gene plays an important role in the response to glyphosate.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Several plants with different levels of natural glyphosate tolerance have been identified (Boerboom et al 1990;Culpepper 2006;DeGennaro and Weller 1984;Huang et al 2014;Owen and Zelaya 2005;Westhoven et al 2008;Yuan et al 2001). Among them, D. chinensis survived glyphosate at 3.3 kg ha -1 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been shown that Arabidopsis plants transformed with an Arabidopsis EPSPS gene driven by the CaMV35S promoter was tolerant to glyphosate [ 37 ]. In another study, it was shown that a an EPSPS gene from Convolvulus arvensis driven by the CaMV35S promoter also conferred resistance to glyphosate in Arabidopsis [ 38 ]. The Arabidopsis transformants in either study, were not checked for EPSPS protein levels relative to the control plants thus making it difficult to compare the outcome of the present study with those previous studies [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%